Immune checkpoint inhibitors–induced large vessel vasculitis: clinical characteristics and management from a European multicentre study - Cottu, Adrien; Delaval, Laure; Forestier, Alexandra; Tomelleri, Alessandro; Campochiaro, Corrado; Bond, Milena; Dion, Jérémie; Gury, Aline; Savary, Xavier; Dhote, Robin; Betrains, Albrecht; Bouillet, Laurence; et al. (Rheumatology (Oxford, England), 2025)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment but frequently cause immune-related adverse events (IrAEs). ICI-induced large vessel vasculitis (LVV) is a rare IrAE, with limited available data. We aimed to describe and compare clinical characteristics and evolution of ICI-induced LVV to primary LVV. This retrospective, multicentre European study included adult patients who developed LVV after ICI therapy between March 2018 and August 2024. Patients were compared with matched controls with primary LVV. LVV was defined histologically and/or morphologically. Twenty-seven patients were included [median (interquartile range) age 68 (61-74) years]. Five (19%) had a history of polymyalgia rheumatica or GCA. Median time from ICIs initiation to LVV diagnosis was 3 (2-17) months. Eight patients (30%) received ipilimumab-nivolumab combination therapy, all of whom developed LVV within 6 months. Most clinical features were similar to matched controls, however PET scan diagnosis and large-vessel involvement were more common in ICI-induced LVV. Visual loss occurred in 4 (15%) patients. Management included discontinuation of ICIs in 19 (70%) patients and administration of glucocorticoids. After a median follow-up of 12 (5-20) months, 20 (74%) achieved sustained remission. Relapse or treatment failure of LVV occurred in 3/9 (33%) patients who continued ICIs and 4/18 (22%) who discontinued them. By last follow-up, 9 (33%) patients had died, mainly from cancer (n = 8). ICI-induced LVV is a rare, early-onset IrAE. Although continuation of ICIs may affect LVV outcomes, cancer progression remains the primary cause of mortality. Prospective studies are warranted to better balance therapeutic approaches.